EXPLORING ENTREPRENEURIAL SELF-EFFICACY CONCEPT: A LITERATURE REVIEW - Darma Rika Swaramarinda; Badrul Isa; Norhayati Mohd Yusof; Mohd Ali Bahari Abdul Kadir (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This paper is part of an ongoing doctoral study exploring the entrepreneurial self-efficacy concept. This paper aims to form a concept relevant to entrepreneurial self-efficacy and gain the theoretical basis to support this conceptualization. For this paper, the researcher analyzed and investigated the literature as a first step to better understand the concept under study properly. This literature review revealed the informative, critical, and valuable synthesis of a particular topic. Moreover, it can be seen from comparing and synthesizing the kinds of literature or the results of previous studies. The contribution of this paper is to provide new perspectives according to the analysis of those kinds of literature relates to entrepreneurial self-efficacy and its subconstructs. The result obtained is that the entrepreneurial self-efficacy construct is built based on sub-constructs, namely own skills, personal traits, initiating investor relationships, and gained knowledge. Subconstructs can also be described in several keywords, which can distinguish one subconstruct from another. It also identified areas of controversy or debate to formulate further research.